CD21– CD27– Atypical B Cells in a Pediatric Cohort Study: An Extensive Single Center Flow Cytometric Analysis - Corrente, Francesco; Terreri, Sara; Palomba, Patrizia; Capponi, Claudia; Mirabella, Mattia; Perno, Carlo Federico; Carsetti, Rita (Frontiers in Pediatrics, 2022)
Atypical B cells (atBCs) are a distinct B-cell population and represent approximately 5% of B cells in peripheral blood (PB) of healthy adult individuals. However, in adults these cells are expanded in conditions of chronic infections, inflammation, primary immunodeficiencies, autoimmune diseases and aging. Their immunophenotype is characterized by the lack of CD21 expression and the hallmark human memory B-cell marker CD27. In this study, we investigated the immunophenotype of atBCs in different pediatric pathological conditions and correlated their expansion with the children’s clinical diagnosis. We were able to retrospectively evaluate 1571 consecutive PB samples, corresponding to 1180 pediatric patients, by using a 9-color flow-cytometric panel. The results, compared with a pediatric healthy cohort, confirmed an expansion of atBCs in patient samples with percentages greater than 5% of total B cells. Four subpopulations with different expression of IgM and IgD were discriminated: IgM+IgD+, IgM+-only, IgD+-only and IgM–IgD–. IgG+ atBCs were predominant in the IgM– IgD– subpopulation. Moreover, the study highlighted some features of atBCs, such as a low CD38 expression, a heterogeneity of CD24, a high expression of CD19 and a large cell size. We also demonstrated that an increase of atBCs in a pediatric cohort is correlated with immunodeficiencies, autoimmune, inflammatory and hematological disorders, consistently with previous studies mainly performed in adults. Furthermore, our flow cytometric clustering analysis corroborated the recent hypothesis of an alternative B origin for atBCs.